Comparison of gut microbial signatures associated with colorectal cancer across two different sample collection datasets - Ha, Thi Thu Cong; Nguyen, Thao Hien; Pham, Thi Tuyet Nhung; Tran, Thi Thanh Tam (Vietnam Journal of Biotechnology, 2026)
Colorectal cancer (CRC) is among the most prevalent cancers globally and in Vietnam. Diagnosing CRC is challenging due to difficulties in tumor detection, leading to thousands of deaths annually. CRC has been demonstrated to be linked with alterations in gut microbial composition and function. Various bacterial taxa have been recognized as potential biomarkers of CRC and suspected to play a crucial role in colon carcinogenesis. This pilot study explores consistent and divergent bacterial signatures in the fecal microbiota of 15 CRC patients compared to 12 healthy individuals in two different sample collection datasets. Both datasets proceeded with the same DNA extraction method, followed by amplification of the 16S rRNA gene's hypervariable regions (V3-V4), and then sequenced with Illumina MiSeq sequencing platform at two different time points. Our findings show that the gut microbiota's alpha and beta diversity did not differ statistically significantly between the healthy individuals and the CRC patients in either dataset. We observed 12 genera in the first dataset and 13 genera in the second dataset that exhibited significant differential abundance between CRC patients and healthy controls. However, due to the small sample size, after adjustment for multiple testing, only Peptostreptococcus and Fusobacterium in Dataset 1, and Parvimonas in Dataset 2, remained significantly associated with CRC according to ANCOM-BC2. Notably, Parvimonas was also detected in CRC patients but not in healthy controls in Dataset 1. This genus may potentially be used as fecal biomarker for CRC detection in Vietnamese patients. Additionally, our study underscores the importance of validating fecal bacterial biomarkers across different sample collection datasets to improve the accuracy and effectiveness of CRC diagnosis and treatment, potentially advancing personalized treatment approaches for Vietnamese patients.